Rural Women Involvement in Oil Palm Value Chain in Akwa Ibom State, Nigeria - Akaninyene, Obot; Maurice, Ozor; P, Anunobi Chizoba (Canadian Journal of Agriculture and Crops, 2022)
The study examined the involvement of rural women in oil palm value chain activities in Akwa Ibom State, Nigeria. Data was collected from two hundred and ten (210) respondents purposively selected from rural oil palm women farmers in Akwa Ibom State. Collected data was analyzed using frequencies, percentage and ranking method. The results showed that the respondents were in their prime age (youthful age/active age) 26-50 years of age. Majority of the respondents also had formal education (primary, secondary or tertiary). Furthermore, most of the respondents (63.8%) were married as that served as labor for the oil palm value chain activities. Also, most of the respondents had a household size of 1-5 persons. A greater percentage of the respondents equally had 11-20 years experiences in oil palm business. In assessing the oil palm value activities the respondents were involved in, the result revealed that the respondents were actively involved in the processing, marketing and storage of the oil palm business. They were less involved in the planting and harvesting of the palm fruits which was more cumbersome and manly. Among the constraints, lack of finance was identified as the topmost constraint to risk, high cost of labor, high cost of transportation, theft etc. The study recommended that government/stakeholders should ensure that the rural women have access to credit and technology to make the business more attractive to the young women.